Evaluation of Bacillus spp. isolated from stingless bee (Heterotrigona itama cockerell) honey as a potential probiotic - Zulkhairi Amin, Fatin Aina (2020)
In Malaysia, stingless bees are well known for producing special honey called “madu kelulut” that is high in antioxidant and antimicrobial activity. Due to its higher moisture content, it provides favourable condition for microbial growth. However, little is known about the types of microbes that resides in this honey. Probiotics are live microbes, which when administered in adequate amounts confer health benefits to the host. This study aimed to find new strains of spore-forming probiotic bacteria from stingless bee (Heterotrigona itama Cockerell) honey. Therefore, Bacillus spp. were isolated from honey produced by 5 different H. itama colonies which were then further identified via 16S rRNA sequencing. Out of 53 isolates, only 23 isolates that are Gram positive, catalase positive and can tolerate 7% NaCl were selected for further molecular identification. Gene sequence analysis revealed that the dominant Bacillus species were Bacillus altitudinis (34%) and Bacillus pumilus (33%) followed by Bacillus megaterium (13%), Bacillus amyloliquefaciens and Bacillus aryabatthai (8%), followed by Bacillus subtilis (4%). Antibacterial activity against pathogenic bacteria assessed using agar well diffusion method showed that B. amyloliquefaciens HTI-19 and B. subtilis HTI-23 have comparable inhibitory activity with commercial probiotic strain Lactobacillus rhamnosus GG. Based on their antibacterial activity, these two strains were evaluated for probiotic properties including acid and bile salt (0.3%) tolerance, hydrophobicity and autoaggregation ability. Both isolates exhibited high tolerance with more than 85% viability in simulated in vitro gastrointestinal (GIT) conditions. Adhesion activity assessed by hydrophobicity and autoaggregation test revealed that B. amyloliquefaciens HTI-19 has the highest autoaggregation ability (84.13%) but lowest hydrophobicity (53.64%) among tested isolates. However, it was not significantly different from L. rhamnosus GG. Both Bacillus spp. were susceptible to all antibiotics with different mode of action. Bacillus amyloliquefaciens HTI-19 was α-hemolytic while B. subtilis HTI-23 exhibited γ-hemolytic activity on blood agar plate. Acute and subacute oral toxicity tests were performed in Sprague-Dawley rats to assess the safety of newly isolated B. amyloliquefaciens HTI-19. The probiotic feeding in acute and sub-acute toxicity study showed no mortality or significant abnormalities in rats throughout the 14-day and 28- ii day experimental period. The rats body weights were not affected by daily administration of probiotic B. amyloliquefaciens HTI-19 except for week 2 of acute study, when the body weight showed significant increase (P<0.05). By gross and microscopic examination of organs, no obvious and significant changes were observed in the morphology of organs from the treated rats. Serum biochemical tests and blood hematology test also revealed no treatment-related changes. Overall, these data indicated that oral administration of B. amyloliquefaciens HTI-19 culture up to 1 x109 CFU/ml for acute and subacute test were safe. The results of this study showed that Bacillus isolates from stingless bee honey, B. amyloliquefaciens HTI-19 and B. subtilis HTI-23, due to its spore forming ability, have remarkable probiotic properties.